Garfield the movie [videorecording (DVD)] - Meyer, Breckin, 1974-; Hewitt, Jennifer Love, 1979-; Tobolowsky, Stephen, 1951-; Arnold, Evan; Lawrence, Mark Christopher, 1964-; Christelle, Vanessa; Davis, Jim, 1945 July 28- (Garfield., 2004)
Garfield's owner, Jon, takes in sweet, but dimwitted pooch Odie, turning Garfield's perfect world upside-down. Now Garfield wants only one thing: Odie out of his home and his life! But when the hapless pup disappears and is kidnapped by a nasty dog trainer, Garfield, feeling responsible, tears himself away from the TV and springs into action.